Efficiency of ganciclovir ophthalmic gel of 0.15% in treatment of acute adenoviral keratconojunctivities - Nadir, Fareya; Islam, M. Robiul; Saifullah, M.; Ashaduzzama, Mohammad; Al Mamun, Abdullah; Basak, Niloy Kumar (International Journal of Research in Medical Sciences, 2024)
Background: Adenoviral eye infection is contagious, self-limiting, causing symptoms like burning, pain, photophobia, and tearing. Diagnosis is clinical; existing treatments lack consistency. Ganciclovir, a selective and less toxic antiviral, shows promise for inhibiting viral DNA synthesis. The primary objective of this study was to assess the efficacy of topical 0.15% Ganciclovir gel in treating adenoviral keratoconjunctivitis, focusing on symptom and sign improvement during the follow-up period. Methods: A study at the National Institute of Ophthalmology and Hospital included 40 adenoviral keratoconjunctivitis patients diagnosed by cornea specialists. Symptoms were scored on a 0-3 scale during a 6-week follow-up. Patients were randomly assigned to group 1 (0.15% ganciclovir) or group 2 (artificial tear control). Data included history and ophthalmic exams. Statistical analyses used SPSS version 13.0 with p<0.05 significance, employing unpaired t-tests and chi-square tests. Results: A study with 40 adenoviral keratoconjunctivitis patients assessed Ganciclovir 0.15% ophthalmic gel efficacy. No age difference between groups was observed. Most patients were male (82.5%), spanning different economic classes. Symptom variations included more foreign body sensation in group 1 and increased watering in group 2. Group 1 exhibited faster symptom improvement over 6 weeks, while group 2 had a slower decline. Both groups experienced complications, but group 1 showed faster recovery, suggesting Ganciclovir's potential efficacy in treating adenoviral keratoconjunctivitis. Conclusions: In summary, the study confirms the effectiveness of 0.15% Ganciclovir gel in treating acute adenoviral keratoconjunctivitis, showing statistically significant and rapid improvement in signs and symptoms.